Attitudes Towards an AI-Augmented Pedagogy in Enhancing English Academic Writing Proficiency: Empirical Evidence from Electrical Engineering Students - Indriati, Titin; Veniati, Veniati; Trionanda, Stevanus; Yahya, Ilham Nur Dimas; Manto, Manto (Universitas Muhammadiyah Mataram, 2026)
This quantitative survey study investigates the perceptions of Electrical Engineering students toward the integration of Artificial Intelligence (AI)-augmented pedagogy in improving English academic writing proficiency. A total of 48 students majoring in electrical engineering at Bangka Belitung State Manufacturing Polytechnic participated in the study. Data were collected through close-ended questionnaires. The data were analyzed using SPSS 25, revealing strong internal consistency (Cronbach’s α = 0.92. The findings revealed that students’ overall attitudes toward the integration of AI were strongly positive (M = 79.69, SD = 11.07), with all three attitudinal dimensions namely cognitive (M = 40.33, SD = 5.18), affective (M = 20.37, SD = 2.97), and behavioral (M = 18.98, SD = 3.34) which also falling within the positive category. These findings reflect the students’ preparedness to engage in technology-supported language learning. Moreover, the study concludes that AI-augmented pedagogy holds significant potential to strengthen students’ academic writing proficiency, particularly in technical and vocational education. Hence, it is recommended that AI tools be integrated into writing instruction while simultaneously fostering the students’ critical digital literacy and sense of ethical awareness.